Conservation and Management of Marine Fishery Resources of Kerala State, India - V. Vijayan, L. Edwin and K. Ravindran (Naga, The ICLARM Quarterly (Vol. 23, No. 3) July-September 2000, 2000)
The highly productive fisheries of Kerala, India, are suffering from overexploitation. Use of unsuitable fishing gears that result in a high level of wasteful bycatch and destruction of egg bearing and juvenile fish should be controlled. This paper makes some suggestions for monitoring and conservation of the fisheries in Kerala.